2017
DOI: 10.1038/ncomms15024
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of APOBEC3A bound to single-stranded DNA reveals structural basis for cytidine deamination and specificity

Abstract: Nucleic acid editing enzymes are essential components of the immune system that lethally mutate viral pathogens and somatically mutate immunoglobulins, and contribute to the diversification and lethality of cancers. Among these enzymes are the seven human APOBEC3 deoxycytidine deaminases, each with unique target sequence specificity and subcellular localization. While the enzymology and biological consequences have been extensively studied, the mechanism by which APOBEC3s recognize and edit DNA remains elusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
266
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(288 citation statements)
references
References 72 publications
19
266
2
1
Order By: Relevance
“…An A3H structural model was generated to help distinguish between these possibilities and inform mutagenesis experiments (Figure 2A). Based on recent A3A/B-ssDNA co-crystal structures (Kouno et al, 2017; Shi et al, 2017), loop 1, loop 7, and active site residues define a positively charged region that is likely essential for A3H to bind single-stranded DNA and potentially also RNA ( i.e ., in this model, the two activities will be inseparable by mutagenesis; patch 1 in Figure 2A). …”
Section: Resultsmentioning
confidence: 99%
“…An A3H structural model was generated to help distinguish between these possibilities and inform mutagenesis experiments (Figure 2A). Based on recent A3A/B-ssDNA co-crystal structures (Kouno et al, 2017; Shi et al, 2017), loop 1, loop 7, and active site residues define a positively charged region that is likely essential for A3H to bind single-stranded DNA and potentially also RNA ( i.e ., in this model, the two activities will be inseparable by mutagenesis; patch 1 in Figure 2A). …”
Section: Resultsmentioning
confidence: 99%
“…The apparent discrepancy between the results in the apo structures and the cocomplexes may be explained by a new hypothesis we propose for the mechanism of substrate binding by A3A, in light of a third structure of an A3–substrate complex reported recently, where human A3F‐CTD was bound to a nonsubstrate Poly_T ssDNA. This complex identified a second nonspecific polynucleotide binding site away from the active site [Fig.…”
Section: Introductionmentioning
confidence: 97%
“…These results suggested that the homodimer interface seen in apo A3A crystal structure may mediate cooperative protein–protein interactions that affect A3A activity. However, cocrystal structures of A3A bound to ssDNA revealed a monomer in the asymmetric unit, with a 1:1 stoichiometry with ssDNA.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be determined whether increased fl A3B activity is due to different catalytic pocket accessibility in the fl A3B than A3B CTD, if the NTD of A3B is better able to guide the ssDNA substrate into the catalytic pocket, if increased processivity enables a more efficient search for potential deamination motifs, or a combination of all of these factors. Recently, it has been shown that A3A and A3B CTD bend the ssDNA substrate in the active site [344,373,374]. How this relates to processivity and if the enzymes can induce the ssDNA bending of larger substrates, such as dynamic ssDNA exposed during replication or transcription remains to be studied.…”
Section: Discussionmentioning
confidence: 99%